Simulasi Area Strategis Dalam Pembangunan Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) Sungai Kerap, Bengkulu Utara - Muhammad Rizky Tanjung; Stevanus Nalendra Jati (Jurnal Ilmiah Lingkungan Kebumian, 2021)
North Bengkulu Regency is an area with various and unique morphological conditions. This is because the location of North Bengkulu itself is located on a row hill which makes it have various morphological reliefs. These unique and varied morphological conditions have the potential for potential micro-hydro power plants (MHP). In the research area, it can be said that the distribution of electricity to remote areas is still not evenly distributed. This research can be the main supporting data in the development of PLTMH for the problems of several villages in North Bengkulu Regency, especially in Kerkap District which still have limited electricity due to inaccessibility of the area. Therefore, it is important to conduct research on the determination of MHP adhesion based on geological aspects. The geological aspects analyzed are the slope morphology around the river and the rock lithology which is the basis for the PLTMH construction. This study uses the AHP (Analysis Hierarchy Process) method which combines several geological parameters that have a certain weight value and after that is applied with data overlay via GIS to obtain a prospect area for a power plant in terms of geology. Overall, this research will be applied to several rivers that have the prospect of building PLTMH, for example in Batang Palik and Sumber rejo villages, Kerkap sub-district, North Bengkulu Regency. Keywords: kerkap. lithology, microhydro, geology, hydrogeology.